FPGA based Implementation of Symmetrical Reduced Switch Multilevel Inverter - K. Venkataramanan; B. Shanthi; T. S. Sivakumaran (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
Multilevel inverter has become more popular and attractive for drive applications. Among the various modulation techniques, Carrier based techniques has been commonly used because of their simplicity and flexibility. This paper presents the comparisons of bipolar multicarrier pulse width modulation for the new symmetrical multilevel inverter. The performance parameters of new multilevel inverter were analyzed through various switching strategies. The detailed study has been carried out by MATLAB/SIMULINK. The real time implementation was carried out using FPGA. The results of both simulation and experimentation were compared.